SOX10: A Useful Marker for Identifying Metastatic Melanoma in Sentinel Lymph Nodes. Issue 2 (February 2015) - Willis, Brian C.; Johnson, Gina; Wang, Jason; Cohen, Cynthia
Abstract : SOX10 (Sry-related HMg-Box gene 10) is a key nuclear transcription factor in the differentiation of neural crest progenitor cells to melanocytes. It has been shown to be a sensitive and specific marker of malignant melanoma of multiple histologic types. We evaluated the immunohistochemical profile of SOX10 in 107 sentinel lymph nodes and compared it to S100 protein, HMB-45, and Melan-A. Seventy-seven lymph nodes originally reported as positive for metastatic melanoma, and 30 reported as negative were reviewed. SOX10 identified metastatic melanoma in 58 of 58 (100%) positive cases included in the final analysis. SOX10 staining showed a statistically significant increase in staining intensity when compared with S100 protein, HMB-45, and Melan-A ( P =0.000, 0.000, and 0.003, respectively). In addition, there was a statistically significant increase in percentage of tumor cells stained by SOX10, compared with S100 protein, HMB-45, and Melan-A ( P =0.015, 0.000, and 0.001, respectively). SOX10 stained nodal nevi in a similar manner to S100 protein and Melan-A in 4 cases. Interpretation of nodal nevus staining (negative by HMB-45) was significantly aided by the crisp nuclear staining produced by SOX10 as compared with the obscuring cytoplasmic staining produced by S100 protein and Melan-A in 3 cases. Identification of micrometastases was facilitated by the nuclear staining pattern of SOX10 and lack of background dendritic cell staining seen in S100 protein. We conclude that given the sensitivity and specificity of SOX10 for detecting metastatic melanoma in sentinel lymph nodes, it is a reliable marker for supplementing and potentially replacing traditionally utilized immunohistochemical stains.